Clinical Characterization of Children Presenting to the Hospital with Enterovirus D68 Infection During the 2014 Outbreak in St. Louis. Issue 5 (May 2016) - Orvedahl, Anthony; Padhye, Amruta; Barton, Kevin; O'Bryan, Kevin; Baty, Jack; Gruchala, Nancy; Niesen, Angela; Margoni, Angeliki; Srinivasan, Mythili
Abstract : Background: The largest known outbreak of enterovirus D68 (EV-D68) infections occurred during 2014. The goal of our study is to characterize the illness severity and clinical presentation of children infected with EV-D68 in comparison to non-EV-D68-human rhinoviruses/enteroviruses (HRV/EV). Method: Our study is a retrospective analysis of severity level, charges and length of stay of children who presented to St. Louis Children's Hospital from August 8, 2014 to October 31, 2014 and tested positive for EV-D68 in comparison to non-EV-D68-HRV/EV–infected patients. Chart review was performed for all EV-D68–infected patients and age and severity matched non-EV-D68-HRV/EV–infected patients. Result: There was a striking increase in hospital census in August of 2014 in our hospital with simultaneous increase in the number of patients with EV-D68 infection. There was no significant difference in severity of illness, length of stay or total charges between EV-D68–infected and non-EV-D68-HRV/EV–infected children. EV-D68 infection was characterized by presenting complaints of difficulty breathing (80%) and wheezing (67%) and by findings of tachypnea (65%), wheezing (71%) and retractions (65%) on examination. The most common interventions were albuterol (79%) and corticosteroid (68%) treatments, and the most common discharge diagnosis was asthma exacerbation (55%). Conclusion: EV-D68 caused a significant outbreak in 2014 with increased hospital admissions and associated increased charges. There was no significant difference in severity of illness caused by EV-D68 compared with non-EV-D68-HRV/EV infections suggesting that the impact from EV-D68 was because of increased number of infected children presenting to the hospital and not necessarily due to increased severity of illness. Abstract : Supplemental Digital Content is available in the text.